2016
DOI: 10.3139/146.111422
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the kinetic behavior of molten aluminum pressureless infiltration into SiC preforms

Abstract: Infiltration of molten metal into ceramic performs without using external force is a new fabrication method for metal-matrix composites. In this research, the kinetics of pressureless infiltration in the processing of Al/SiC composites have been investigated. In order to improve the wettability and infiltration properties, Al-6Mg (wt.%) alloy was prepared. Also, the ceramic component was coated for 15 min using electroless copper plating at a temperature of 60 – 70 °C (pH = 12.5) and a rate of 17 – 20 μm s−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was demonstrated that high SiC volume fraction composites can be produced by infiltrating liquid metals into packed SiC powder. This way was applied at relative low temperatures with aluminum and copper [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that high SiC volume fraction composites can be produced by infiltrating liquid metals into packed SiC powder. This way was applied at relative low temperatures with aluminum and copper [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that high SiC volume fraction composites can be produced by infiltrating liquid metals into packed SiC powder. This way was applied successfully at relative low temperatures with aluminum and copper [15,16]. MMC can be tailored to have superior properties such as enhanced high-temperature performance, high specific strength and stiffness, increased wear resistance, better thermal and mechanical fatigue, and creep resistance than those of unreinforced alloys.…”
Section: Introductionmentioning
confidence: 99%